Exploring the revitalisation of endangered intangible heritage and languages through multimedia storytelling and immersive technologies: a case study of virtual reality and 2D film with the Kusunda community in Nepal - Galeazzi, Fabrizio; Parameswaran, Gayatri; Gaedtke, Felix; Swami, Viren (Frontiers in Computer Science, 2025)
IntroductionReviving Kusunda is a project that explores the utility of immersive storytelling for the revitalisation of an endangered indigenous culture and language in Nepal called Kusunda. As part of this project, we compared the impact of a virtual reality (VR) experience (entitled Kusunda: Speak to Awaken) and a 2D companion film on audience engagement and emotional connections with the personal stories portrayed in both formats.MethodsData were collected through three focus groups conducted in the United Kingdom (n = 15) and three in Nepal (n = 15), as well completion of quantitative surveys by participants in the United Kingdom that were preceded by screenings of both formats (N = 100).ResultsThe qualitative and quantitative results indicated the importance of integrating both VR and 2D film to maximize audience engagement. Specifically, while viewing the 2D film as a group appeared to promote group identity and wider access, the VR format was considered more effective for immersing oneself within the environment and developing an emotional connection, building on an understanding of how members of the Kusunda community live. Similarly, the quantitative results showed that participants found both formats to be highly informative and in terms of knowledge gain, although the VR format was more effective than the 2D format in terms entertainment and enjoyment, and emotional engagement.DiscussionOverall, these results suggest that using a multi-pronged approach that leverages the benefits of both VR and 2D film can be effective in attempts to preserve endangered languages and heritage.